Tinta SePMA - Suhana, Abdul Mutalib; Nurul Shafinaz, Ismail; Mohd Basri, Basir; Nurul Aida, Othman; Noor Fazemil, Naim (Universiti Malaysia Perlis (UniMAP), 2010)
Seminar berlangsung di Dewan Kapitol UniMAP, Kangar, Perlis.